“A stitch in time saves nine” : managing congenital nephrotic syndrome in resource-limited circumstances - Karmila, Abu Bakar; Justin Wang, Qi Yuee; Amalina Huda, Amir Hamzah; Charles, Lai Dekun; Caroline Eng, Siew Yin (Medical Journal of Malaysia, 2022)
We report a case of congenital nephrotic syndrome. Our patient presented with sepsis-like illness and acute kidney injury during the neonatal period. Subsequent urine analysis showed persistent heavy proteinuria with concomitant hypoalbuminaemia and clinical anasarca. Screening for congenital infections was negative. Diuresis was initially induced with daily albumin infusion. Subsequently, administration of furosemide combined with amiloride was adopted as albumin-sparing strategies. Both angiotensinconverting enzyme inhibitor and non-steroidal antiinflammatory drugs were started after 4 weeks of life. Such treatment strategies resulted in a significant reduction in the need for albumin infusion, thus allowing better preservation of the venous estate and improving quality of life with a reduced need for inpatient care.